(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2010)
A 45 years male beggar admitted to this hospital with a huge swelling of scrotum and penis and bipedal nonpitting edema. This swelling was gradually increasing which hampered his personal life. He was previously diagnosed as a case of filarial scrotum and penis. He took diethylcarbamazine (DEC) for 4 years. CFT for filaria was strongly positive but microfilariae in the blood were not detected even after provocative test. Total 15 kg of scrotal penile skin was removed and reconstructed by trunk skin flaps. DOI:10.3329/jbcps.v27i3.4297 J Bangladesh Coll Phys Surg 2009; 27: 173-176